농촌기업생태계 경쟁력 지표 설정 분석 - 이진홍 (한국농촌경제연구원, 2013)
In recent years, transformation of rural industries into high-valued and more complex industries based on agricultural production has been accelerating. The Ministry of Agriculture, Food and Rural Affairs has focused on rural industry development for promoting indigenous local industries, regional agricultural clusters and the food industry. The problems that have surfaced in the rural industry sector are lack of the capitalization effect and the changeover from livelihood-type agriculture to an industrial ecosystem. Thus, measures to build business systems based on endogenous rural vitalization, regional economic growth, and convergence of rural industries are urgently needed. In this situation, this study aims to set up business ecosystems of rural industries based on productivity, robustness and niche creation. Also, we evaluate these factors with 15 agricultural experts using the Analytic Hierarchy Process(AHP). According to the AHP analysis, the niche creation in business ecosystems represents the largest portion at 46.5 percent, followed by the productivity at 31.9 percent and the robustness at 21.5 percent. This study suggests that the basic direction of business ecosystems should be geared toward making them sustainable business by sharing values and saving social capital.
Keywords: 농촌산업; 기업생태계; AHP; Analytic Hierarchy Process; rural industry; business ecosystem; AHP; Analytic Hierarchy Process